2012
DOI: 10.17221/11/2012-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Winter survival of Phytophthora alni subsp. alni in aerial tissues of black alder

Abstract: ABSTRACT:The winter survival of the invasive pathogen Phytophthora alni subsp. alni in black alder stems was studied in the bankside alder stand of the Moravská Dyje River in southern Bohemia after two very different winter seasons: cold in 2008/2009, with the average temperature of -1.96°C, and extremely mild in 2006/2007, with the average temperature of 2.54°C. The difference in these two winters resembles the expected potential climate change in Central Europe in this century. After the cold winter of 2008/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, temperature strongly influences both the pathogen itself, and subsequent impacts of the disease (Schumacher et al ., ). Cold winter conditions, especially involving long periods of heavy frost, seem to significantly reduce the overwintering survival in P. × alni (Černý & Strnadová, ). Similarly, Redondo et al .…”
Section: Interactions With the Biotic And Abiotic Environmentmentioning
confidence: 99%
“…For example, temperature strongly influences both the pathogen itself, and subsequent impacts of the disease (Schumacher et al ., ). Cold winter conditions, especially involving long periods of heavy frost, seem to significantly reduce the overwintering survival in P. × alni (Černý & Strnadová, ). Similarly, Redondo et al .…”
Section: Interactions With the Biotic And Abiotic Environmentmentioning
confidence: 99%
“…xalni is a pathogen with optimal growth temperatures above 22 °C [35,74], one of these factors may be the winter temperature in soil, water and bark. In this regard, a study conducted by Černý and Strnadová [75] in the Czech Republic, the country considered in this study with the highest incidence of LOH events, showed that the winter survival of P. xalni in necrotic bark tissue of black alder (Alnus glutinosa) is very limited. Soil properties, in particular pH [74,76], might also be potential sources of stress.…”
Section: Discussionmentioning
confidence: 89%